Effects of limit-feeding finishing swine on performance and carcass measurements - W Zook; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1982)
Two feeding trials with 138 crossbred pigs with an average initial weight of 129 pounds were conducted to determine the effects of limit feeding on average daily gain, feed efficiency and carcass measurements. Pigs were fed either ad libitum, restricted to 80 or 85% of ad Iibitum intake, or restricted to 2, 4 or 8 hours access to self-feeders. Average daily gain was decreased (P<.05) by reducing feed intake to 80 or 85% of ad Iibitum, and restricting pigs to 2, or 4 hours access to feed. Pigs allowed 8 hours access to feed gained at the same rate, with similar feed intake as pigs fed ad Iibitum. Feed efficiency was not different for any of the restricted fed treatments. However, pigs restricted to 80% of ad Iibitum had the best feed efficiency. Barrows and gilts responded similarly to restricted feeding.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Limit-feeding; Finishing swine; Performance; Carcass measurements